The Dwelling Panel – A New Research Method for Studying Urban Change - Friedrichs, Jürgen; Blasius, Jörg (Raumforschung und Raumordnung | Spatial Research and Planning, 2015)
Classical panel studies, such as the German Socio-Economic Panel (GSOEP), the US Panel Study of Income Dynamics (PSID), and the British Household Panel Study (BHPS), are based either on households or persons in households. Any attempts to break down such data into smaller spatial units such as neighbourhoods, due migration and changes in a specific sample can only be described by the stayers and the out-movers. With the exception of new members in stayer households, there is no information on households moving into a given neighbourhood. Consequently, when using classical panel data, it is not possible to analyse appropriately changes in small areas. In order to solve the problem of population changes in small spatial units such as neighbourhoods, we recommend using an alternative sampling unit: instead of households, we suggest focusing on dwellings and houses. The dwelling panel allows us to examine processes, such as gentrification, poverty and voting behaviour in small urban areas. Drawing on an ongoing study, we shall discuss methodological issues and show how a dwelling panel can be constructed and maintained in several waves. In the process, we shall discuss panel attrition and compare possible replacement strategies in classical panels with those in dwelling panels.